2006
DOI: 10.1002/jso.20533
|View full text |Cite
|
Sign up to set email alerts
|

Application of modern imaging methods in diagnosis of gallbladder cancer

Abstract: The poor prognosis of gallbladder cancer (GBC) is related to its dissemination capacity and usually late diagnosis due to its non-specific clinical appearance. Recent improvements in hepatobiliary surgery have underlined the importance of an early specific diagnosis, which requires a multidisciplinary approach and, when possible, specialized equipment. The first step in an early diagnosis is to identify patients in the appropriate epidemiological setting (e.g., incidental finding, chronic cholecystitis) for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
2
26

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(118 citation statements)
references
References 69 publications
(142 reference statements)
0
87
2
26
Order By: Relevance
“…Sonography is often the first imaging technique (10). CT and MRI are widely used for further characterization of potentially malignant gallbladder lesions and metastatic survey (11).…”
Section: Resultsmentioning
confidence: 99%
“…Sonography is often the first imaging technique (10). CT and MRI are widely used for further characterization of potentially malignant gallbladder lesions and metastatic survey (11).…”
Section: Resultsmentioning
confidence: 99%
“…It is combined with CT to produce a whole body metabolic map of glucose uptake. A previous study reported that (FDG-PET)-CT has a sensitivity of 56% for detecting omental, peritoneal, or lymphatic spread of GBC [2]. A general drawback of FDG-PET is the possibility of a falsepositive result due to detection of inlammatory areas instead of a tumor, because they both have high glucose uptakes.…”
Section: Updates In Gallbladder Diseasesmentioning
confidence: 99%
“…The anatomy of the gallbladder, speciically the absence of a serosal layer between it and the liver, permits the relative early invasion of GBC into the liver [1]. GBC also tends to spread both to lymph nodes and hematogenously to the peritoneal surfaces [2]. Moreover, because of its nonspeciic presentation and constellation of symptoms and signs, many of which it shares with benign diseases such as biliary colic or chronic cholecystitis, GBC tends to go undiagnosed until relatively later stages [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nishiyama et al adopted dual-time-point FDG-PET to evaluate the nature of gallbladder lesions, and demonstrated that delayed FDG-PET was more helpful than early FDG-PET in the evaluation of malignancy, because of the increased uptake by lesions, and the increased lesion-to-background contrast [12] . Recent hybrid PET-CT systems provide structural and functional information simultaneously, and may offer early and accurate staging with an improved specificity [13,14] .…”
mentioning
confidence: 99%